Pregnancy outcome of external cephalic version in singleton pregnancy with breech presentation at term - Mishra, Rajesh Kumar; Vardhan, Shakti; Singh, Sanjay; Panda, Swati Sagarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Breech delivery is associated with poor perinatal outcomes irrespective of the route of delivery. External cephalic version can be a useful tool in management of breech presentation at term by converting it to a cephalic presentation. A study was conducted to evaluate maternal and neonatal outcome of external cephalic version in singleton pregnancies with breech presentation in third trimester. Methods: A prospective observational study was carried out at a tertiary care hospital over a period of 2 years. This study included a total of 65 uncomplicated cases of breech presentation who fulfilled the inclusion criteria. External cephalic version was carried out after 36 weeks of period of gestation in primigravida and after 37 weeks in multigravida women. These patients were followed up till delivery and data was collected and analysed regarding the mode of delivery, maternal and fetal outcome. Results: External cephalic version was successful in 41 patients with a success rate of 63%. Out of them, vaginal delivery could be achieved in 31 cases (75.6%) and LSCS was done for rest of the 10 cases. The success rate was higher in multigravida ladies compared to primigravida ladies. No major procedure related adverse event was noticed in our study. Conclusions: External cephalic version is a very safe and easy procedure which can reduce the rate of cesarean delivery in singleton pregnancies with breech presentation. The results of this study are in favor of wider practice of this procedure in selected cases.